The Hasidic spirit as the foundation of the art of Marc Chagall - Bagraim, Abigail Sarah (Rhodes University, Faculty of Humanities, Department of Fine Art, 1987)
In considering Chagall's art the observer is immediately struck by the constancy of his almost obsessive repetition of certain symbols and themes. In this way Chagall has created his own fantasy world, one with which the observer soon becomes acquainted and grows to love and understand.
Keywords: Chagall, Marc, 1887-1985 -- Criticism and interpretation